Nutritional Status of the Cancer Patients Receiving Chemotherapy in an Oncology Centre, Nepal - Dawadi, Bijaya; Joshi, Sarala; Mishra, Tulasi Adhikari (Nepal Journal of Health Sciences, 2024)
Introduction: Chemotherapy affects the nutritional status of cancer patients. Side effects of anticancer therapies can lead to inadequate nutrient intake and subsequent malnutrition. Nutrition is an important factor in treatment, affects patient’s mortality and morbidity. Objective: The study was carried to find nutrition status of cancer patients receiving chemotherapy and determinants of nutrition status. Methods: Descriptive, cross sectional study was carried out with sample of 198 cancer patients (>18 years) receiving chemotherapy. Data was collected using face to face interview technique using modified Patient Generated Subjective Global Assessment and Karnofsky Performance Scale tool. SPSS was used for data analysis, descriptive and Inferential statistics to find determinants of malnutrition. Results: The mean age was 52 ± 14.13 years, 21.7% were anaemic before and 24.7 were anaemic after administration of chemotherapy. Unexpected weight loss and Karnofsky performance score were determinants of nutritional status. Karnofsky Performance Score was significantly associated with nutrition status with AOR of 7.308 (CI=2.593-20.592). Similarly, Unexpected weight loss was significantly associated with nutrition status with AOR of 10.733 (CI= 1.378-83.623). Conclusions: Large number of cancer patients receiving chemotherapy were malnourished. Unexpected weight loss and Karnofsky performance score were significant factors for nutrition status maintenance. Therefore, nutrition intervention program should be targeted to improve these factors for intervention.